2000
DOI: 10.1128/jvi.74.18.8382-8389.2000
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Retroviral DNA Integration and Gene Expression

Abstract: Although retroviruses can integrate their DNA into a large number of sites in the host genome, factors controlling the specificity of integration remain controversial and poorly understood. To assess the effects of transcriptional activity on integration in vivo, we created quail cell clones containing a construct with a minigene cassette, whose expression is controlled by the papilloma virus E2 protein. From these clones we derived transcriptionally active subclones expressing the wild-type E2 protein and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 39 publications
10
39
1
Order By: Relevance
“…13 Addition of the transcription factor HNF3 inhibited ASLV end joining at the HNF3 sites. 13 This together with previous data that showed that ASLV integration does not favour transcriptionally active sites 14 would have predicted the Mitchell findings and it is nice to see this so comprehensively confirmed.…”
Section: What Guides the Integration Event?supporting
confidence: 71%
“…13 Addition of the transcription factor HNF3 inhibited ASLV end joining at the HNF3 sites. 13 This together with previous data that showed that ASLV integration does not favour transcriptionally active sites 14 would have predicted the Mitchell findings and it is nice to see this so comprehensively confirmed.…”
Section: What Guides the Integration Event?supporting
confidence: 71%
“…The viral primer (U3-RAV, described in ref. 8, ATCGTCGTGCACAGT-GCCTTT) primes from the antisense strand of RAV-1 U3 LTR sequences, and amplifies an integration product that includes the last 106 bp of the 5Ј end of the integrated provirus. The genomic primer (CACCACCACGGCACTATAAAT) was specific for sequences near the transcription start site of the quail MT gene.…”
Section: Pcr Assay To Detect In Vivomentioning
confidence: 99%
“…The PCR assay used to detect region-specific integration products was adapted from that used in previous studies in our laboratory (3,8), and it was done as follows. Genomic DNA isolated from QT6 cells uninfected, infected and induced with 100 g of ZnSO 4 , or infected and uninduced was diluted to 1 g͞ml, heated at 100°C for 5 min, and then placed in an 80°C heating block until addition to the PCR mixture.…”
Section: Pcr Assay To Detect In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Integration is an obligate step in productive retrovirus infection (Weidhaas et al, 2000;Maxfield et al, 2005). Integration of the retroviral DNA into the host cell genome requires the interaction of the retroviral integrase protein with the outer ends of both viral long-terminal repeats (LTRs), thereby removing two nucleotides from the 3¢ ends (3¢ processing), and the newly created 3¢OH attacking a phosphate of the target DNA (strand transfer) (Engelman et al, 1991;Craigie, 2001;Vandegraaff and Engelman, 2007;Delelis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%